PENGARUH MOTIVASI BELAJAR DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR KETERAMPILAN TATA BUSANA SISWA KELAS XII SEKOLAH LUAR BIASA (SLB) DI KOTA MAKASSAR - Asra Ali; Hamidah Suryani; Aisyah Hading (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2022)
This study is a quantitative study that aims to determine: 1) the effect of learning motivation on learning outcomes of fashion skills; 2) the influence of independent learning on learning outcomes of fashion skills; 3) the influence of learning motivation and learningindependence on learning outcomes of special school fashion skills. The samples in this study were students of class XII Special Schools (SLB) in Makassar City, namely SLB Negeri 1 Makassar, SLB-B YPPLB Makassar and SLB YPAC Makassar a total of 24 students. Research data obtained through documentation, interviews, and questionnaires. The data were processed using descriptive statistical analysis with regression analysis. The results of the study show that 1) learning motivation has a significant effect on learning outcomes for fashion skills with an R Square value of 16.9%. 2) learning independence has a significant effect on learning outcomesof fashion skills with an R Square value of 16.3%. 3) learning motivation and learning independence together have a significant effect on learning outcomes of fashion skills with an R Square value of 26.4% and have the influence of other variables of 73.6% influenced by other factors outside this study.